Genetic Association of Broiler (Gallus Gallus domesticus) Treated with a Disease Blocking Extract - Nwankudu, Oluchi Nnenna; Ifenkwe, Daniel Chidi (British Journal of Healthcare and Medical Research, 2025)
Broiler birds whose meat is considered healthy are assailed with diseases from hatch. However, vaccination protocols have been established to contain viral diseases. Unfortunately, bacterial diseases still menace poultry. In order to contain bacterial diseases, poultry farmers often abuse antibiotics and may not heed withdrawal periods before such birds are presented to consumers to purchase which sequels a community of poultry consumers unknowingly suffering from drug resistance. Guava leaf extract (GLE) is rich in phytochemicals. Therefore, this research was set up to assess the potential of guava leaf extract to block bacterial and viral diseases of poultry. Methods: A total of fifty day old chicks was procured. Forty were unvaccinated while 10 positive control) were vaccinated. They were acclimatized for one week. The 50 birds were divided into 5 groups of 10 birds per group. Group 1; 10 vaccinated birds. Group 2: unvaccinated untreated (negative control). Groups 3-5 were treated with 400mg/kg of GLE per os; daily, once in 7 days and once in 14 days respectively. Any death during the course of 13 weeks were microbially cultured. At 13th week, blood was collected from the birds for haematology and serology. Blood was also collected from 3 birds picked at random from groups 1, 2 and 4 for gene extraction. Result: There was gene modification of broiler birds treated with GLE which presented itself as gene deletions, insertions and single nucleotide polymorphism. The result of the microbial culture of dead birds incriminated klebsiella; an opportunistic bacteria as the main cause of death in groups 1 and 2. Differential white blood cell count showed heterophils significantly (P ≤ 0.05) higher in guava leaf treated groups, but there was no established disease and no death. Serology showed GLE treatment led to significant (P ≤ 0.05) increase in High Density Lipoprotein, significant (P ≤ 0.05) decrease in Cholesterol, Aspartate aminotransferase, Alanine aminotransferase and creatinine. Conclusion: Guava leaf extract is healthy and successfully blocked bacterial and viral diseases of poultry.